Self-assembled and pyrolyzed carbon aerogels: an overview of their preparation mechanisms, properties and applications. Issue 34 (6th August 2015) - Allahbakhsh, Ahmad; Bahramian, Ahmad Reza
Abstract : Recent advances in the fabrication mechanisms, structures and applications of different classes of carbon aerogels are comprehensively reviewed. Abstract : An overview of the synthesis conditions and mechanisms for the fabrication of different types of carbon aerogels, as well as the structural and functional properties of these materials, is presented here. In this overview, carbon aerogels are classified into three major categories: (i) conventional pyrolyzed organic-based carbon aerogels, which are products of the pyrolysis process of organic aerogels; (ii) self-assembled carbon aerogels, which are products of a reduction process; and (iii) nanocomposite carbon aerogels. Synthesis mechanisms for the sol–gel process of organic aerogels are reviewed using different mechanisms suggested in the literature. Moreover, the overall fabrication process of self-assembled carbon aerogels (graphene and carbon nanotube aerogels) is covered and the suggested mechanism for the gelation process of self-assembled carbon aerogels during the reduction process is investigated using reported mechanisms. The structural performance and functional properties (electrochemical and thermal properties) of different types of carbon aerogels are covered in detail. Moreover, different structural features of carbon aerogels and the influence of synthesis conditions on these structural characteristics are assessed and compared. Based on the literature results covered in this review paper, carbon aerogels are perfect candidates for the fabrication of ultra-low density supercapacitors, as well as thermal insulating materials.